ANALISIS PENGELOLAAN ALOKASI DANA DESA DALAM PEMBERDAYAAN MASYARAKAT DESA KARANGLUHUR KABUPATEN WONOSOBO - Feni Yudanti Prasetyaningtyas (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
Analysis of Village Fund Allocation Management in Community Empowerment Karangluhur Village Wonosobo regency is one of the Government's efforts in improving the welfare of the village community and making the villages to be independent with all their potential. The use of Village Fund Allocation is aimed at making the Village more independent and creative and not dependent on the Village Government. The purpose of this study is to illustrate and know the Management of Village Fund Allocation in Community Empowerment and Factors Affecting the Management of Village Fund Allocation in Community Empowerment. The research method used was descriptive method with the qualitative approach which used Milles Huberman analytical method. The results of research shows that at the Planning Stage of Karangluhur Village community plays an active role in providing input to the Village Government to build the Village. At the stage of Budgeting is done based on the priority scale of village needs. Stages of Karangluhur Village Government Mechanism has been implemented in accordance with the rules that have been determined. In the Stages of Use for Community Empowerment activities, the funds obtained are still less than for the Village Operations and BPD, which are mostly used for personnel expenditures, in addition to the Community Development activities in Karangluhur Village mostly only in the form of material aid or stimulant aid. On the Supervision and Accountability done by the Local Government and the internal Government of the Village in the form of Letter of Accountability. The factors that influence the Village Fund Allocation Management in the Village Community Empowerment either from Internal and External Government Karangluhur Village.